Operations Management / Second Edition - Greasley Andrew (Harlow, England John Wiley & Sons, Ltd, 2006)
Preface, Acknowledgements, Introduction, Operations Strategy, Design, Process Types, Layout Design, Facility Design and Location, Process Technology, Product and Service Design, Process Design, Job and Work Design, Management, Planning and Control, Capacity Management, Inventory Management, Lean Operations and JIT, Enterprise Resource Planning, Supply Chain Management, Project Management, Quality, Performance Measurement and Improvement, Glossary, Index.